2014
DOI: 10.1123/ijsnem.2013-0191
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Different Doses of Calcium Lactate on Blood pH, Bicarbonate, and Repeated High-Intensity Exercise Performance

Abstract: We investigated the effects of low- and high-dose calcium lactate supplementation on blood pH and bicarbonate (Study A) and on repeated high-intensity performance (Study B). In Study A, 10 young, physically active men (age: 24 ± 2.5 years; weight: 79.2 ± 9.45 kg; height: 1.79 ± 0.06 m) were assigned to acutely receive three different treatments, in a crossover fashion: high-dose calcium lactate (HD: 300 mg · kg(-1) body mass), low-dose calcium lactate (LD: 150 mg · kg(-1) body mass) and placebo (PL). During ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 29 publications
3
17
1
5
Order By: Relevance
“…Van Montfoort et al (2004) showed a small improvement in exercise tolerance in a continuous run-to-exhaustion protocol lasting~80 s, while Morris et al (2011) showed that acute lactate ingestion improved exercise performance by 17% in a supramaximal exercise tolerance test following four repeated maximal exercise bouts. In contrast to these findings, an investigation from our group did not show any ergogenic effect of acute lactate ingestion on repeated supramaximal exercise, although minor increases in blood bicarbonate were shown (Painelli et al, 2014b). Since the exercise protocol used by Painelli et al (2014b) was highly acidotic and sensitive to detect performance improvements elicited by increased blood buffering capacity (Artioli et al, 2007;Tobias et al, 2013), these results have cast some doubt as to whether lactate is an effective buffering agent.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Van Montfoort et al (2004) showed a small improvement in exercise tolerance in a continuous run-to-exhaustion protocol lasting~80 s, while Morris et al (2011) showed that acute lactate ingestion improved exercise performance by 17% in a supramaximal exercise tolerance test following four repeated maximal exercise bouts. In contrast to these findings, an investigation from our group did not show any ergogenic effect of acute lactate ingestion on repeated supramaximal exercise, although minor increases in blood bicarbonate were shown (Painelli et al, 2014b). Since the exercise protocol used by Painelli et al (2014b) was highly acidotic and sensitive to detect performance improvements elicited by increased blood buffering capacity (Artioli et al, 2007;Tobias et al, 2013), these results have cast some doubt as to whether lactate is an effective buffering agent.…”
mentioning
confidence: 56%
“…In contrast to these findings, an investigation from our group did not show any ergogenic effect of acute lactate ingestion on repeated supramaximal exercise, although minor increases in blood bicarbonate were shown (Painelli et al, 2014b). Since the exercise protocol used by Painelli et al (2014b) was highly acidotic and sensitive to detect performance improvements elicited by increased blood buffering capacity (Artioli et al, 2007;Tobias et al, 2013), these results have cast some doubt as to whether lactate is an effective buffering agent. One possible explanation for the lack of a positive effect with lactate could be related to the use of acute supplementation protocols since their alkalinizing effects are transient, meaning that blood pH and bicarbonate return to baseline levels shortly after ingestion (Painelli et al, 2014b;Siegler et al, 2010).…”
mentioning
confidence: 56%
“…Key words: buffering, wingate upper-body, muscle fatigue and physical performance. Sanguíneas ................................................................................. 40 4.7 Análise Estatística ..................................................................................................... 41 ................................................................................................... 43 6.1 (ARTIOLI et al, 2007;LINDH et al, 2008;SIEGLER e HIRSCHER, 2010 (ARTIOLI, et al, 2007;PAINELLI et al, 2014;TOBIAS et al, 2013 Isso ajuda na manutenção do pH intramuscular e possibilita a manutenção do desempenho no exercício de alta intensidade (HOBSON et al, 2012). processo contrátil e sobre a via glicolítica, levando ao retardo do aparecimento da fadiga (BISHOP et al, 2004).…”
Section: Agradecimentosunclassified
“…Contudo, apenas um estudo apresentou resultados positivos, com uma grande melhora de 25% no desempenho aeróbio (AZEVEDO et al, 2007). No entanto, como há aumento dos níveis de pH (FAHEY et al, 1991;MORRIS, et al, 2011;PAINELLI et al, 2014) e bicarbonato (FAHEY et al, 1991;PAINELLI et al, 2014) (MCNAUGHTON, et al, 1999), pois pode promover um incremento maior no bicarbonato sanguíneo com o maior período de suplementação, mas esse protocolo ainda precisa ser explorado. Os dados estão apresentados como média ± desvio-padrão.…”
Section: Suplementação De Bicarbonatounclassified
See 1 more Smart Citation